Developing an "Islamic Environmental Fiqh": A Theological Response to the Climate Crisis by the Indonesian Ulama Council (MUI) - Siti Nuri Nurhaidah; Habib Nabiel Al Musawa; Muhammad Haris Hakam; Usman Umar; Solahuddin Solahuddin (Islamic Studies in the World, 2025)
Background. The climate crisis is not only an ecological challenge but also a theological one, especially in countries where religion plays a significant role in shaping public behavior and policy. In Indonesia, the world's largest Muslim-majority country, the Indonesian Ulema Council (MUI) has begun formulating "Islamic Environmental Jurisprudence" as a religious response to environmental degradation. Purpose. This study aims to analyze the theological foundations, interpretative strategies, and practical implementation of the environmental jurisprudence developed by the MUI in addressing climate change. Methods. Using qualitative content analysis, this study examines fatwas, religious documents, and public statements issued by the MUI between 2010 and 2024. Results. The research findings indicate that the MUI's environmental jurisprudence integrates Qur'anic ecological ethics, principles of maslahah (public interest), and sustainability-oriented ijtihad. Furthermore, it reflects a contextual understanding of sharia in responding to the global ecological crisis. Conclusion. This study concludes that the MUI initiative is a progressive model of religious environmentalism, which has the potential to influence Muslim public discourse and environmental policy, both nationally and globally.